The Role of School Backpack and Training Habits on Development of Spinal Pain among Iranian Primary Student - Mashallah Aghilinejad; Saber Mohammadi; Amir Bahrami-Ahmadi; Marjan Amini; Elaheh Kabir-Mokamelkhah; Shahrbanoo Moslemi (Iranian Journal of Health, Safety and Environment, 2019)
In the recent studies, some variables such as weight of the school backpack, how to carry it or backpack features are currently under study in relation with low back pain (LBP) among students. The present study aimed to assess the role of school backpack and training habits on the development of spinal pain among Iranian students. A current cross-sectional study was performed between November 2015 and April 2016 on 616 primary school children with age between 11-13 years in Karaj city, Iran. We gathered information on demographic characteristics and ergonomic data on backpacks via a specific checklist. The Nordic Musculoskeletal Questionnaire (NMQ) to determine the prevalence of spinal complaints was used among the participants. To assess the ergonomic status of backpacks, the students were asked to carry with the consistent and conventional method. Study findings showed that unfortunately, only 1.9% of students carried their bags correctly. Musculoskeletal complaints in the neck region were significantly higher among students who do their homework on the floor in compare with students that doing their homework behind the desk. Musculoskeletal complaints in the shoulder region of students had a significant association with Bag handle type, TV & game time, doing homework position, Bag use with 2 ropes and Bag weight/body weight. Findings of the present study recommended that we need to step up public health strategies and develop a monitoring system that is both preventative and proactive.